Creeping flow with non-uniform viscosity in a permeable industrial conduct. (2016) - Hona, Jacques; Nyobe, Elisabeth Ngo; Pemha, Elkana
The creeping flow occurs through a straight horizontal conduct formed by two coaxial cylinders fixed at different temperatures. The problem is governed by the vorticity equation coupled to the energy equation due to the variation of the dynamic viscosity with temperature. The results about the wall shear stress obtained from the numerical integration reveal the existence of the cusp type bifurcation. Under certain values of control parameters, the suction which manifests itself as the mass withdrawal phenomenon causes important variations of temperature near the walls. Thus, the maxima of thermal gradients are located at the walls. The temperature is almost constant around the centre of the flow region; this behaviour involves in certain circumstances the presence of a large area of inflection in the temperature distribution through the annular conduct. The dominance of flow reversal on wall suction agrees with the behaviour of pressure gradients.